Development of a Wireless PC-Controlled Mobile Robot System and Multimedia Based Learning Module - Mujber, Tariq Saad (2001)
Autonomous mobile robots, which are required to operate safely in ill-defined, complex and time varying environments, are essential elements in achieving improved performance and flexibility in manufacturing. In this thesis, a mobile robot system was designed and fabricated. The system consists of two main sections; namely; system hardware and system software. The system hardware includes motion system, receiver and transmitter, and video camera, all these components are controlled wireless using personal computer. The main purpose of the video camera is to enable the user to monitor the movement of the mobile robot system. The system software includes the development of a user-friendly and flexible interface control code named PC-Mobile Robot Control (PC-MRC). The code has been developed using Object-Oriented Programming Language and Graphic User Interface. The developed control algorithms enable the user to control the mobile robot manually, automatically or by voice recognition commands. There are three ways to control the mobile robot manually (Manual Run, Path Run and Paths Run). For automatic-run, the mobile robot can be controlled using two ways (Run File and Timer). Voice recognition control is also installed and commissioned in the developed robot system. The developed control software has been tested by running experimental movements of the robot in two different directions (forward and backward) and the time and the velocity were recorded. Three different types of motion systems (tracks, legs, wheels) were tested. It has been found that in all motion system types, the backward movement is faster than the forward movement by a range of 2% to 5.5%. It has also been found that in both movements (forward and backward) the wheels motion system is faster than the tracks and legs motion systems. Multimedia technology provides a valuable resource to enhance the teaching and learning experience. The ability to combine practical applications and visualization is among the advantages of technology based training and teaching. In this study a multimedia module for robot teaching and training was developed and implemented using Macromedia Director 7 as authoring tool. The multimedia module is divided into three main sections, which are automation, robotics and mobile robot systems. The mobile robot section shows the fabrication of the mobile robot, construction of gripper arm and some video of the movement of the mobile robot system. The implementation of this multimedia-based learning for robot technology will help to enhance the learning abilities of the engineering students. Hence, it will help to complement the subject and its understanding.